Network Pharmacology and Experimental Evidence Reveal Dioscin Suppresses Proliferation, Invasion, and EMT via AKT/GSK3b/mTOR Signaling in Lung Adenocarcinoma - Mao W; Yin H; Chen W; Zhao T; Wu S; Jin H; Du B; Tan Y; Zhang R; He Y (Dove Medical Press, 2020)
Wenli Mao,1,* Heng Yin,2,* Wenya Chen,1,* Tingxiu Zhao,1 Shaofeng Wu,3 He Jin,1 Biaoyan Du,1 Yuhui Tan,2 Ren Zhang,2,3 Yanli He1,3 1Department of Pathology and Pathophysiology, School of Basic Medical Sciences, Guangzhou University of Chinese Medicine, Guangzhou 510006, People’s Republic of China; 2Department of Medical Biotechnology, School of Basic Medical Sciences, Guangzhou University of Chinese Medicine, Guangzhou 510006, People’s Republic of China; 3Research Center for Integrative Medicine of Guangzhou University of Chinese Medicine, Guangzhou University of Chinese Medicine, Guangzhou 510006, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanli He; Ren Zhang Tel +86 20-39358015; +86 20-39358007 Fax +86 20-39358020Email blhhh@gzucm.edu.cn; zren@gzucm.edu.cnPurpose: Dioscin, a natural glycoside derived from many plants, has been proved to exert anti-cancer activity. Several studies have found that it reverses TGF-β 1-induced epithelial–mesenchymal transition (EMT). Whether dioscin can reverse EMT by pathways other than TGF-β is still unknown.Methods: We used network-based pharmacological methods to systematically explore the potential mechanisms by which dioscin acts on lung cancer. Cell Counting Kit-8 assay, scratch healing, Transwell assay, Matrigel invasion assay, immunofluorescence assay, and Western blotting were employed to confirm the prediction of key targets and the effects of dioscin on EMT.Results: Here, using network-based pharmacological methods, we found 42 possible lung cancer-related targets of dioscin, which were assigned to 98 KEGG pathways. Among the 20 with the lowest p-values, the PI3K-AKT signaling pathway is involved and significantly related to EMT. AKT1 and mTOR, with high degrees (reflecting higher connectivity) in the compound-target analysis, participate in the PI3K-AKT signaling pathway. Molecular docking indicated the occurrence of dioscin-AKT1 and dioscin-mTOR binding. Functional experiments demonstrated that dioscin suppressed the proliferation, migration, invasion, and EMT of human lung adenocarcinoma cells in a dose-dependent manner, without TGF-β stimulation. Furthermore, we determined that dioscin downregulated p-AKT, p-mTOR and p-GSK3β in human lung adenocarcinoma cells without affecting their total protein levels. The PI3K inhibitor LY294002 augmented these changes.Conclusion: Dioscin suppressed proliferation, invasion and EMT of lung adenocarcinoma cells via the inactivation of AKT/mTOR/GSK3β signaling, probably by binding to AKT and mTOR, and inhibiting their phosphorylation.Keywords: dioscin, lung adenocarcinoma, epithelial–mesenchymal transition, network-based pharmacology